2022
DOI: 10.13057/biodiv/d231158
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of native freshwater fish from Brantas River, East Java, Indonesia

Abstract: Abstract. Hasan V, Mamat NB, South J, Ottoni FP, Widodo MS, Arisandi P, Isroni W, Jerikho R, Samitra D, Faqih AR, Simanjuntak CPH, Mukti AT. 2022. A checklist of native freshwater fish from Brantas River, East Java, Indonesia. Biodiversitas 23: 6031-6039. This study aims to provide information on the freshwater fish species composition of the Brantas River, the second-largest river in Java, Indonesia. All samples used in this study were the caught activities during Fish Resource Survey (form May 5, 2021 to Aug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 32 publications
(34 reference statements)
0
10
0
Order By: Relevance
“…Thus, the fish population in the rivers is well maintained. Hasan et al (2022) reported that rivers close to shrimp ponds and settlements have lower diversity because they are polluted by human activities, which have changed the natural function of the river.…”
Section: Fish Compositionmentioning
confidence: 99%
“…Thus, the fish population in the rivers is well maintained. Hasan et al (2022) reported that rivers close to shrimp ponds and settlements have lower diversity because they are polluted by human activities, which have changed the natural function of the river.…”
Section: Fish Compositionmentioning
confidence: 99%
“…All samples of mangrove snails were put into a sample box and immediately preserved in 96% alcohol (Hasan et al 2019b;Hasan et al 2023). For longer preservation, all specimens were transferred to 10% formalin (Serdiati et al 2021;Hasan et al 2022b). Identification of mangrove snails was carried out by observing morphological characteristics such as shell shape, shell width, shell length, shell color, apex, whorl, whorl body, siphonal canal, spire, suture, aperture, and columella.…”
Section: Sampling and Identification Of Mangrove Snailsmentioning
confidence: 99%
“…Indonesian waters, with their expansive area, harbor a diverse array of biological resources (that can enhance the local community's economic income) (Hasan and Widodo 2021;Indarjo et al 2022;Hasan et al 2022;Meiryani et al 2023;Serdiati et al 2023), both domestically and internationally (Gani et al 2021;Ndobe et al 2023;Indarjo et al 2022;Hasan et al 2023;Nurjirana et al 2023). This condition also applies to the waters of Tarakan Island (Indarjo et al 2023a).…”
Section: Introductionmentioning
confidence: 99%